Phenylalanine hydroxylase variants interact with the co-chaperone DNAJC12 - Jung, Kunwar; Himmelreich, Nastassja; Blau, Nenad (Human mutation, 2019)
DNAJC12, a type III member of the HSP40/DNAJ family, has been identified as the specific co-chaperone of phenylalanine hydroxylase (PAH) and the other aromatic amino acid hydroxylases. DNAJ proteins work together with molecular chaperones of the HSP70 family to assist in proper folding and maintenance of intracellular stability of their clients. Autosomal recessive mutations in DNAJC12 were found to reduce PAH levels, leading to hyperphenylalaninemia (HPA) in patients without mutations in PAH. In this work, we investigated the interaction of normal wild-type DNAJC12 with mutant PAH in cells expressing several PAH variants associated with HPA in humans, as well as in the Enu1/1 mouse model, homozygous for the V106A-Pah variant, which leads to severe protein instability, accelerated PAH degradation and mild HPA. We found that mutant PAH exhibits increased ubiquitination, instability, and aggregation compared with normal PAH. In mouse liver lysates, we showed that DNAJC12 interacts with monoubiquitin-tagged PAH. This form represented a major fraction of PAH in the Enu1/1 but was also present in liver of wild-type PAH mice. Our results support a role of DNAJC12 in the processing of misfolded ubiquitinated PAH by the ubiquitin-dependent proteasome/autophagy systems and add to the evidence that the DNAJ proteins are important players both for proper folding and degradation of their clients.
Gesehen am 24.05.2019